The effect of internal controls on financial reporting quality in Iranian family firms. Issue 3 (2nd September 2019) - Lari Dashtbayaz, Mahmoud; Salehi, Mahdi; Safdel, Toktam
Abstract : Purpose: The purpose of this paper is to investigate the relationship between internal controls weakness and financial reporting quality and the effect of family ownership on the mentioned relationship in Iranian listed firms. Design/methodology/approach: In this way, the authors included the number of 139 firms from 2013 to 2017, of which 28 were family firms. The hypotheses are analyzed based on panel data and means comparison. Findings: The results illustrated that weakness in internal controls has a significant negative relationship with financial reporting quality. In other words, internal controls weakness decreases the quality of financial reporting quality. Moreover, the results showed that being familial does not affect the aforementioned relationship. Originality/value: Consequently, there is no suitable criteria to distinguish family firms and there is a need to take them into serious consideration because very few studies have been conducted focusing on this issue in Iran, as it is considered an argumentative subject to be discussed in the Iranian market.